2011
DOI: 10.1016/j.eurpolymj.2011.02.025
|View full text |Cite
|
Sign up to set email alerts
|

An alternative solvent system for the steady state electrospinning of polycaprolactone

Abstract: Polycaprolactone (PCL) is a biocompatible aliphatic polyester with many possible applications in the medical field. PCL nanofibres, produced by electrospinning, could provide new characteristics that are of interest for these applications. However, a key prerequisite is the ability to obtain bead-free fibres with diameters in the nanoscale range. At present the most commonly used solvent for electrospinning PCL is chloroform, but this only leads to fibres in the microscale range. Therefore various solvent syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
139
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(168 citation statements)
references
References 49 publications
12
139
0
Order By: Relevance
“…Nanofibrous structures have a small pore size, a bulky specific surface area and a high sponginess, making them an attractive material for medical applications [7,24]. 2 of 8 Electrospinning is a widely accepted technique used to prepare polymer nanofibers, where ultrafine fibers in nanoscale can be collected after an emission of the polymer solution is ejected in an electrical field with high voltage [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Nanofibrous structures have a small pore size, a bulky specific surface area and a high sponginess, making them an attractive material for medical applications [7,24]. 2 of 8 Electrospinning is a widely accepted technique used to prepare polymer nanofibers, where ultrafine fibers in nanoscale can be collected after an emission of the polymer solution is ejected in an electrical field with high voltage [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This allowed for the demarcation of a steady state region within the steady state table presenting the possible combinations of solvent ratio and polymer concentration for which a steady state is possible. This methodology has been used previously to verify the steady states for electrospinning different types of polyamides (De Vrieze et al 2008De Schoenmaker et al 2012) and polycaprolactones (Van der Schueren et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…To achieve steady state electrospinning, it is crucial to determine a suitable solvent system Van der Schueren et al 2011). By studying steady state electrospinning of polyamides, it was possible to produce large uniform membranes that were further studied for use in water filtration (Bjorge et al 2009;Daels et al 2010Daels et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Van der Schueren et al used chloroform and mixture of acetic acid and formic acid as solvent and after comparing the results, they observed that the fibers' diameter for the mixture solvent system was ten times smaller than the case in which the chloroform was used. 30 The main reason of changed fiber average diameter can be attributed to the difference in solvent dielectric constant (Table 3), as the solvent properties strongly affect the morphology of the fibers. In this regard, Lee et al examined the effects of solvents of methylene chloride, a mixture of methylene chloride and dimethylformamide as well as a mixture of methylene chloride and toluene, and found that the fiber average diameter of methylene chloride was about 5500 nm, and for a mixture of methylene chloride and dimethylformamide was equal to 200 nm.…”
Section: The Structure and Morphologymentioning
confidence: 99%
“…31 With a plurality of investigations done by researchers about solvent types in PCL electrospinning, it was announced that fiber diameter was strongly dependent on the solution concentration or amount of PCL ( Figure 6 and Table 4). 28,30,32 By changing the fiber's diameter, porosity and pore size were also changed. Scaffolds with larger diameter has higher porosity and larger pore size.…”
Section: The Structure and Morphologymentioning
confidence: 99%